Student cluster competition 2017, team Nanyang Technological University : reproducing vectorization of the Tersoff multi-body potential on the Intel Broadwell architecture - Liu, Siyuan (2020)
Reproducing previous work plays an important role in validating its effectiveness under different experiment settings. In this paper, we reproduce the results from the paper “The vectorization of the Tersoff multi-body potential: an exercise in performance portability” [1]. In particular, we reproduce the accuracy of the reduced precision solvers, the speed-up of the vectorized implementation, and the strong scaling test using Intel Xeon E5-2699 v4 Broadwell CPUs. We show that our reproduced results match the claims made in the original paper.